A Male Case of Kagami-Ogata Syndrome Caused by Paternal Unipaternal Disomy 14 as a Result of a Robertsonian Translocation - Wang, Xiaoxue; Pang, Hui; Shah, Birju A.; Gu, Hongcang; Zhang, Lijun; Wang, Hua (Frontiers in Pediatrics, 2020)
Kagami–Ogata syndrome (KOS) is a rare imprinting disorder characterized by skeletal abnormalities, dysmorphic facial features, growth retardation and developmental delay. It is caused by paternal uniparental disomy 14 [upd(14)pat] as well as epimutations or microdeletions affecting the paternally derived chromosome 14q32.2 imprinted region. Until now, about sixty cases of Kagami–Ogata syndrome have been reported. Remarkably, only six cases presented with upd(14)pat harboring Robertsonian translocation (ROB), among which two cases were familial. Here, we reported a male infant presenting with clinical manifestations of facial dysmorphism, bell-shaped small thorax and omphalocele. Meanwhile, he is the only male case who has been reported so far. A balanced ROB involving the long arms of chromosomes 13 and 14 was identified in both the patient and his father. Upd(14)pat was confirmed by DNA polymorphic markers studies. In conclusion, our case report provides a new male case of Kagami–Ogata syndrome caused by upd(14)pat with paternally inherited Robertsonian translocation. KOS as the result of upd(14)pat and ROB is rare, characteristic clinical manifestations need to be concerned and cytogenetic/molecular studies should be performed.